Arteriovenous Malformation of The Mandible : A Rare Case Report - Hitarthi Kubavat; Bhavin Dudhia; Pritesh Ruparelia (Wolters Kluwer Medknow Publications, 2005)
Arteriovenous malformations (AVMs) are extremely rare conditions that can result from congenital or acquired abnormalities in the structure of blood vessels. They are potentially fatal. AVMs may be asymtomatic or may show various signs and symptoms including soft tissue swellings, pain, changes in skin and mucosal colour, erythematous and bleeding gingiva, bruit and paresthesia. Radiographically, there are no pathognomic features. The present case illustrates an AVM in a 25-year-old male with history of trauma to mandible and no characteristic signs (except a swelling) suggesting AVM.